Fiabilidad de los recursos filosóficos y humanísticos: propuesta de un nuevo protocolo de actuación - Muñoz-alonso López, Gemma (Revista General de Información y Documentación, 2010)
The critical assessment of the information existing is an unavoidable task, both for professionals an information consumers in the philosophic and humanistic field. This work presents a study of the evaluation proposals of information sources, carried by specialists in the subject. Also, this work establishes the master lines of an innovative evaluation protocol.